Influence of Body Mass Index in Pregnancy on Maternal and Fetal Outcome - Sumaiya Farooq, Sanobar Baloch, Shazia Awan, Fakharunissa (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obesity in women is on the rise, which is a serious public health issue. Researchers have shown that these changes have a significant influence on pregnancy outcomes in these women, as confirmed by several studies. Objectives: To examine the relationship of the body mass index (BMI) in pregnancy with the feto-maternal outcome Material Methods: We surveyed 230 women for this study, which was both prospective and cross-sectional. The study covered all pregnant women who met the inclusion criteria. At least 16 weeks into the pregnancy, the singleton pregnancy must have a complete medical record to be eligible. Throughout the first trimester, researchers measured and calculated the BMI of pregnant women. Using the formula kg/m2, the body mass index (BMI) of an individual can be calculated. According to the Asian-Pacific cutoff points8, BMI was divided into four categories: underweight ( 18.5 kg/m2), normal weight (18.5-22.9 kg/m2), overweight and obesity (23–26.9 kg/m2), and obese (>25 kg/m2). SPSS version 23.0 was used to analyse all of the data. Results: A total of 230 women were selected in this study. Out of these, 30 (13%) were underweight (less than or equal to 18.5kg/m2), 124 (54%) belonged to normal BMI (>18.5 -24.9 kg/m), while 50 (22%), 21 (9%) and 5 (2%) women were from the overweight (25-29.9 kg/m2), obese (30-34.9 kg/m2) and the morbidly obese (> 35 kg/m2) categories respectively. Increasing BMI was associated with an increase in gestational diabetes (GDM) and pre-eclampsia. However, BMI >18.5 kg m2 had an adjusted odds ratio of 0.21 (95 percent CI 0.22, 0.68) for pre-eclamptic syndrome and GDM and appeared to influence the development of these complications. This was a protective effect. Overweight and obese women were more likely to give birth through instrumental delivery, with ORs of 3.4 (95 % CI, 1.1, 22.2) and 3.5, respectively (95 % CI 0.3, 15.8). A severely obese woman was more likely to have a large-gestational-age baby as her weight increased. The odds ratio for underweight women having babies that are smaller than average for their gestational age (SGA) is 5.7 (95 % CI 6.2, 9.2). Conclusion: According to the findings of this study, 50% of pregnant women had abnormal BMIs. Several pregnancy issues might arise for women with an abnormally high BMI, such as preeclampsia, gestational diabetes, cesarean section, inducement of labor, and macrosomic newborns with obesity and anemia.